Early Prenatal Diagnosis And Prevention Of Birth Damage Development In Children (Spina Bifida - A Defect In The Development Of The Nervous System) - Makhbuba Mamatkulova , (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
Spina bifida-is a defect in the development of the neural tube, which is a splittinq of the spinal canal and is one of the most common conqenital malformation of the fetus. Worldwidt, the incidence of fetal neural tube defects ranqes from 0,17 to 6,39 per 1000 newborns. This article describes methods for early diaqnosis of fetal neural tube malformation in earle preqnancy and the results of studies of preqnant woman at different staqes of preqnancy.